Comparison of the Distributions of Urocortin Containing and Cholinergic Neurons in the Perioculomotor Midbrain of the Cat and Macaque - May, Paul J. (2008)
Urocortin is a novel neurotransmitter that appears to play a role in eating and drinking behavior. Most urocortin-positive (urocortin(+)) neurons in rodents are found in the cytoarchitecturally defined Edinger-Westphal nucleus (EW). However, the EW is traditionally described as the source of the preganglionic parasympathetic outflow to the ciliary ganglion. We examined the distribution of urocortin(+) cells and motoneurons by use of immunohistochemical staining for this peptide and for choline acetyl transferase (ChAT) in macaque monkeys, where most preganglionic motoneurons inhabit the EW, and in cats, where most do not. In both species, lack of overt double labeling indicated the ChAT(+) and urocortin(+) cells are separate populations. In the monkey, most non-oculomotor ChAT(+) neurons were found within the EW. In contrast, urocortin(+) cells were mainly distributed between the oculomotor nuclei, and in the supraoculomotor area. In the cat, most non-oculomotor ChAT(+) cells were located in the supraoculomotor area and anteromedian nucleus. Few were present in the cat EW. Instead, this nucleus was filled with urocortin(+) cells. These results highlight the fact the term EW has come to indicate different nuclei in different species. Consequently, we have adopted the identifiers preganglionic (EW(PG)) and urocortin containing (EW(U)) to designate the cytoarchitecturally defined EW nuclei in monkeys and cats, respectively. Furthermore, we propose a new open-ended nomenclature for the perioculomotor (pIII) cells groups that have distinctive projections and neurochemical signatures. This will allow more effective scientific discourse on the connections and function of groups like the periculomotor urocortin (pIII(U)) and preganglionic (pIII(PG)) populations.